Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1029/2006jd007696
|View full text |Cite
|
Sign up to set email alerts
|

Energetic particle precipitation effects on the Southern Hemisphere stratosphere in 1992–2005

Abstract: [1] Measurements from several different satellite instruments are used to estimate effects of energetic particle precipitation (EPP) on NO x (NO + NO 2 ) in the Southern Hemisphere stratosphere from 1992 to 2005. The focus is the EPP Indirect Effect (IE), whereby NO x produced in the mesosphere or thermosphere via EPP (EPP-NO x ) descends to the stratosphere during the polar winter, where it can participate in catalytic ozone destruction. EPP-NO x entering the stratosphere is found to vary in magnitude from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
246
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(271 citation statements)
references
References 64 publications
19
246
2
Order By: Relevance
“…They then used a chemistry general circulation model to simulate surface temperature response to geomagnetic activity variations by realistically varying the A p index to further explore the mechanisms leading to the temperature responses reported earlier by Rozanov et al [2005]. The A p -driven NO x parameterization that they used in their model had previously proved to be realistic and in a good agreement with observations [Baumgaertner et al, 2009], concurring well with earlier observations of the relationship between polar middle atmosphere NO x concentrations and the variation in geomagnetic activity and particle precipitation [Siskind et al, 2000;Randall et al, 2007;Seppälä et al, 2007;Sinnhuber et al, 2011]. Baumgaertner et al [2011] showed the temperature response from 0.01 hPa to 1000 hPa (mesopause to surface) when the model was forced with the A p -controlled EPP-NO x (their Figure 9).…”
Section: Introductionsupporting
confidence: 71%
“…They then used a chemistry general circulation model to simulate surface temperature response to geomagnetic activity variations by realistically varying the A p index to further explore the mechanisms leading to the temperature responses reported earlier by Rozanov et al [2005]. The A p -driven NO x parameterization that they used in their model had previously proved to be realistic and in a good agreement with observations [Baumgaertner et al, 2009], concurring well with earlier observations of the relationship between polar middle atmosphere NO x concentrations and the variation in geomagnetic activity and particle precipitation [Siskind et al, 2000;Randall et al, 2007;Seppälä et al, 2007;Sinnhuber et al, 2011]. Baumgaertner et al [2011] showed the temperature response from 0.01 hPa to 1000 hPa (mesopause to surface) when the model was forced with the A p -controlled EPP-NO x (their Figure 9).…”
Section: Introductionsupporting
confidence: 71%
“…While the effect caused by SEP events in the upper atmosphere is more or less known (Randall et al, 2007;Seppälä et al, 2008;Egorova et al, 2011;Rozanov et al, 2012), its possible influence on the lower atmosphere is still unclear. Previous phenomenological studies (Mironova et al, 2008(Mironova et al, , 2012 yielded that there is a small, marginally detectable effect of an extreme SEP (e.g., such as the one of 20 January 2005) on the aerosol particles in the lower-middle polar stratosphere during stable winter/summer conditions.…”
Section: A Mironova and I G Usoskin: Effect Of Ground Level Enhmentioning
confidence: 99%
“…These nitrates are seen to migrate downwards over time (Siskind et al 2000;Funke et al 2005), resulting in catalytic destruction of stratospheric ozone (Callis et al 2000). Large SEP events generate considerable transient polar ozone depletions, which persist in winter until UV irradiance of the polar stratosphere resumes (Jackman et al 2006(Jackman et al , 2008Randall et al 2005Randall et al , 2007. Recently, Seppälä et al (2009) reported changes in polar surface temperatures which they associate with large SEP events.…”
Section: ''Top-down'' Solar Forcingmentioning
confidence: 99%